Dynamic adaptive X‐ray optics. Part II. High‐speed piezoelectric bimorph deformable Kirkpatrick–Baez mirrors for rapid variation of the 2D size and shape of X‐ray beams. (7th December 2018) - Alcock, Simon G.; Nistea, Ioana-Theodora; Signorato, Riccardo; Owen, Robin L.; Axford, Daniel; Sutter, John P.; Foster, Andrew; Sawhney, Kawal
Abstract : Demonstrated here is the first simultaneous high‐speed beamline operation of a pair of piezoelectric bimorph deformable Kirkpatrick–Baez mirrors for the rapid and repeatable change and stabilization of the vertical and horizontal size of a synchrotron X‐ray beam within only a few seconds. This enables continuous adaptive shaping of the X‐ray beam in almost real time. Such innovations could lead to a major scientific change in how deformable X‐ray mirrors are used at synchrotron and X‐ray free‐electron laser sources. Abstract : The tangential curvature of actively bent X‐ray mirrors at synchrotron radiation and X‐ray free‐electron laser (XFEL) facilities is typically only changed every few hours or even days. This operation can take tens of minutes for active optics with multiple bending actuators and often requires expert guidance using in situ monitoring devices. Hence, the dynamic performance of active X‐ray optics for synchrotron beamlines has historically not been exploited. This is in stark contrast to many other scientific fields. However, many areas of synchrotron radiation and XFEL science, including macromolecular crystallography, could greatly benefit from the ability to change the size and shape of the X‐ray beam rapidly and continuously. The advantages of this innovative approach are twofold: a large reduction in the dead time required to change the size of the X‐ray beam for different‐sized samples and the possibility of making multiple changes to the beam during the measurement of a single sample. In the preceding paper [Part I; Alcock, Nistea, Signorato & Sawhney (2019), J. Synchrotron Rad. 26, 36–44], which accompanies this article, high‐speed visible‐light Fizeau interferometry was used to identify the factors which influence the dynamic bending behaviour of piezoelectric bimorph deformable X‐ray mirrors. Building upon this ex situ metrology study, provided here is the first synchrotron radiation beamline implementation of high‐speed adaptive X‐ray optics using two bimorphs operating as a Kirkpatrick–Baez pair. With optimized substrates, novel opto‐mechanical holders and a next‐generation high‐voltage power supply, the size of an X‐ray beam was rapidly and repeatedly switched in <10 s. Of equal importance, it is also shown that compensation of piezoelectric creep ensures that the X‐ray beam size remains stable for more than 1 h after making a major change. The era of high‐speed adaptive X‐ray optics for synchrotron radiation and XFEL beamlines has begun.